The Role of Farmer Groups in Managing Rice Farming Businesses in Wuasa Village North Lore District - Jody Setyadi; Failur Rahman; RitaYunus; Meity Ferdiana Paskual; Santi Yunus (ProBisnis : Jurnal Manajemen, 2024)
Research objectives This is To know how big the role group farmer is in the management of rice farming in the village of Wow North Lore District, Poso Regency. Wuasa Village owns fertile land​ suitable For Budi Power paddy, so part big residents Work as farmers. This is the background writer. For the research role, group farmers to farming rice in the village Wow. Study This adopts a qualitative method with a descriptive approach. Data is collected through interviews, observations, and documentation. Research results show that the role group the farmer in the management of farming paddy's impact is significant to the development farming public. And active in implementation activity farming, especially For searching and distributing information, collaborating with government or institutions related to providing facility production and planning activity for group farmers.